2001
DOI: 10.1016/s0928-8244(00)00247-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of virulence factors, cell components and adhesion in Helicobacter pylori-mediated iNOS induction in murine macrophages

Abstract: To investigate the mechanisms involved in Helicobacter pylori-mediated inducible nitric oxide synthase (iNOS) upregulation in mononuclear cells we cocultivated human THP-1 acute monocytic leukemia cells and murine J774A.1 professional macrophages with different H. pylori wild-type strains and mutants. We have shown that H. pylori-mediated iNOS induction in J774A.1 is independent of established virulence factors but dependent on direct interaction between bacteria and cells. In J774A.1, iNOS was equally upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The current work extends this suggestion to other pro‐inflammatory processes associated with Helicobacter infection, such as those mediated by macrophages. These processes appear to be independ‐ent of the presence of a functional Cag PAI in H. pylori strains (Assmann et al , 2001; Maeda et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The current work extends this suggestion to other pro‐inflammatory processes associated with Helicobacter infection, such as those mediated by macrophages. These processes appear to be independ‐ent of the presence of a functional Cag PAI in H. pylori strains (Assmann et al , 2001; Maeda et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although live H. pylori or its lipopolysaccharide (LPS) fails to induce NO production by human macrophages [24, 25], several groups have demonstrated NOS2 mRNA induction in human gastric epithelial cell lines after H. pylori infection [26-28]. However, in several of these studies, either: (i) the level of NOS2 induction is very low [26, 29]; (ii) the production of RNI does not reflect NOS2-dependent high-output NO generation – e.g., ~ 6 μM NO 2 − produced by AGS cells infected for 24 h with H. pylori [27]; or (iii) NO production is not shown in these papers [26, 28].…”
Section: The Mechanism Of Nos2 Induction In Host Cells By H Pylorimentioning
confidence: 99%
“…The novelty of the H. pylori –innate immune system response crosstalk resides mainly in the fact that H. pylori LPS is not effective in inducing macrophage NO generation [25, 32, 33], in contrast to the endotoxin of other Gram-negative bacteria [32, 34]. When live H. pylori is in direct contact with murine macrophages, a strong NOS2 induction and a high level of NO production are observed in the cells [32, 35].…”
Section: The Mechanism Of Nos2 Induction In Host Cells By H Pylorimentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous in vitro studies have investigated both the adherence of H. pylori to gastric epithelial cells, 12,14–17 and the ability of H. pylori to induce IL‐8 production following adherence of this gastric pathogen 18–23 . Recent reports have suggested that FCS can modify the cytoskeletal changes induced by H. pylori within epithelial cells and may modulate the adherence of H. pylori to epithelial cells 12 .…”
Section: Discussionmentioning
confidence: 99%